2020
DOI: 10.1111/ajr.12665
|View full text |Cite
|
Sign up to set email alerts
|

Conducting community rehabilitation review sessions via videoconference: A feasibility study

Abstract: Objective To determine the feasibility of conducting a single videoconferencing session (telerehabilitation) instead of a face‐to‐face home visit for a review appointment in a community rehabilitation program. Design A feasibility study based on Bowen's framework was used to determine demand, acceptability, limited efficacy and practicality of telerehabilitation. The study involved qualitative and quantitative data analysis. Setting Two Victorian community rehabilitation programs providing services to large ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…25 To address these barriers, both patients and therapists likely require support and education in the use of new technology. 26 Physical limitations and restrictions to socialising and face-to-face rehabilitation appeared to limit participants' incidental activity, with participants mostly limited to light domestic activities. In the short term, reductions in physical activity may lead to poorer mental health and wellbeing.…”
Section: Qualitative Finding Convergence With Quantitative Findingmentioning
confidence: 99%
See 1 more Smart Citation
“…25 To address these barriers, both patients and therapists likely require support and education in the use of new technology. 26 Physical limitations and restrictions to socialising and face-to-face rehabilitation appeared to limit participants' incidental activity, with participants mostly limited to light domestic activities. In the short term, reductions in physical activity may lead to poorer mental health and wellbeing.…”
Section: Qualitative Finding Convergence With Quantitative Findingmentioning
confidence: 99%
“…Education and resources on the use of communication technologies could help to increase the uptake of these technologies, by older people and therapists, to facilitate community reintegration following hospitalisation. 26 These resources could be useful during the COVID-19 pandemic and also following the pandemic for older people who are socially isolated and/or have limited access to rehabilitation services, such as those living remotely, those with impairments that limit their travel, and those who are immunocompromised. Policies supporting the provision of telehealth, such as the recent extension of funding for telehealth services through the Medicare Benefits Schedule, 32 should also provide incentive for health providers to increase the use of communication technologies in their clinical practice.…”
Section: Qualitative Finding Convergence With Quantitative Findingmentioning
confidence: 99%
“…52 A recent study demonstrated that 25% of people receiving home-based rehabilitation were suitable for telerehabilitation and that telerehabilitation was a feasible, acceptable and efficient way of delivering community rehabilitation to people from outer metropolitan and rural areas. 53 Provided sufficient infrastructure is in place to support implementation, telerehabilitation models thus appear promising in this context. 53 In the present study, the majority of community rehabilitation services were found to provide physiotherapy and occupational therapy, with only a low proportion of services reporting to have input from medical, nursing or allied health disciplines such as dietetics, and social work.…”
Section: Outpatient Rehabilitation Services-summary Of Key Findings and Implicationsmentioning
confidence: 99%
“…53 Provided sufficient infrastructure is in place to support implementation, telerehabilitation models thus appear promising in this context. 53 In the present study, the majority of community rehabilitation services were found to provide physiotherapy and occupational therapy, with only a low proportion of services reporting to have input from medical, nursing or allied health disciplines such as dietetics, and social work. This suggests that the majority of current community service provision is focused primarily on mobility and activities of daily living.…”
Section: Outpatient Rehabilitation Services-summary Of Key Findings and Implicationsmentioning
confidence: 99%
“…For example, consultations with these professionals often require physical assessments and interactions, prescription of exercise, inspection of the environment or in‐depth psychological interactions requiring building of rapport. While studies have shown that telehealth can be feasible and effective in these types of services (Hwang et al., 2017; Speyer et al., 2018; Wundersitz et al., 2020) large studies of the consumer perspective or examination of different telehealth modalities in these settings are lacking (Iacono et al., 2016).…”
Section: Introductionmentioning
confidence: 99%